Normal and Tangential Drag Forces of Nylon Nets, Clean and with Fouling, in Fish Farming. An Experimental Study - Yarko Niño (Water, 2020)
Experiments in a laboratory tank have provided measurements of the normal and tangential drag forces exerted on flat nets for different flow conditions. From those forces, normal and tangential drag coefficients of the nets have been obtained as functions of the Reynolds number and the solidity index. The experiments used two types of nets employed in the operation of a cultivation center: the fish net and the sea lion net, for the clean situation and for real operating conditions, with fouling adhered to the nets. Polyethylene ropes were used to characterize the presence of fouling in the nets. The experiments were carried out to determine equations for the normal and tangential drag coefficients. For the normal drag coefficient, the equations are linear with the Reynolds number, and the coefficients of the equations are linear with the solidity index. The equations are not so accurate for the tangential drag coefficient. The Reynolds number is not a relevant parameter for this coefficient and neither is the solidity index for the fish net, but the coefficient grows slightly with it for single and double sea lion nets with fouling. The literature review on the drag forces of nets reports that the tangential drag force is around 30% of the normal drag force. This value is approximately an average value of the ratio for the sea lion net and is higher for the clean fish net in this article.